Genome organization of epidemic Acinetobacter baumannii strains - Triassi Maria; Giannouli Maria; Rocco Francesco; Di Nocera Pier; Zarrilli Raffaele (BMC Microbiology, 2011)
Abstract Background Acinetobacter baumannii is an opportunistic pathogen responsible for hospital-acquired infections. A. baumannii epidemics described world-wide were caused by few genotypic clusters of strains. The occurrence of epidemics caused by multi-drug resistant strains assigned to novel genotypes have been reported over the last few years. Results In the present study, we compared whole genome sequences of three A. baumannii strains assigned to genotypes ST2, ST25 and ST78, representative of the most frequent genotypes responsible for epidemics in several Mediterranean hospitals, and four complete genome sequences of A. baumannii strains assigned to genotypes ST1, ST2 and ST77. Comparative genome analysis showed extensive synteny and identified 3068 coding regions which are conserved, at the same chromosomal position, in all A. baumannii genomes. Genome alignments also identified 63 DNA regions, ranging in size from 4 o 126 kb, all defined as genomic islands, which were present in some genomes, but were either missing or replaced by non-homologous DNA sequences in others. Some islands are involved in resistance to drugs and metals, others carry genes encoding surface proteins or enzymes involved in specific metabolic pathways, and others correspond to prophage-like elements. Accessory DNA regions encode 12 to 19% of the potential gene products of the analyzed strains. The analysis of a collection of epidemic A. baumannii strains showed that some islands were restricted to specific genotypes. Conclusion The definition of the genome components of A. baumannii provides a scaffold to rapidly evaluate the genomic organization of novel clinical A. baumannii isolates. Changes in island profiling will be useful in genomic epidemiology of A. baumannii population.